Contribution of Psychopathy to Delinquents' Affective Attachment - Čačić, Sandra; Gavrilović-Jerković, Vesna (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
The main objective of this research is to determine whether psychopathy contributes to delinquents’ attachment. By using factor analysis, four factors have been separated, which have been used later in order to operationalise psychopathy: antisocial behaviour, unscrupulousness, affective sensitivity and conscientiousness. Attachment analysis was based on seven attachment organisations: unsolved family traumatisation, fear of loss of external secure base, negative other concept, negative self concept, mentalization, use of external secure base and rage regulation. The research was conducted in two secondary schools in Sombor, the Correctional home for juveniles in Krusevac and the Home for juvenile delinquents in Nis. It includes 524 persons, 421 adolescents and 103 delinquents. Results: Antisocial behaviour, affective sensitivity and conscientiousness are three factors that contribute to the difference between delinquents and non- delinquents regarding the secure base organisation. Furthermore, this means that psychopathic characteristics mentioned above will modify the way and the extent of delinquents' attachment, as well as the way they use their significant others as a secure base and support in stressful situations.